Smart Education for Smart Bangladesh: Perspective of New Curriculum 2021 to Complete Smart Bangladesh Vision 2041. - Moniruzzaman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study investigates what smart education is in the new education curriculum in Bangladesh and shows a relationship between Smart Education and Smart Bangladesh Vision 2041. This study consists of secondary data. Our analysis reveals strong consumption of the new curriculum 2021 and Smart Bangladesh Vision. We conclude that Smart Education means being smart in every way and the mentioned advantages will complete Smart Bangladesh Vision 2041.